In vitro antibacterial activity and mechanism of cell-free supernatant of Bacillus velezensis Ea73 against Streptococcus agalactiae, a predominant bacteria that causes mastitis in cows - Peng, Siqi; Okyere, Samuel Kumi; Cheng, Lin; Tang, Ziyao; Yang, Feng; Liu, Xi; Hu, Yanchun (Frontiers in Veterinary Science, 2025)
Streptococcus agalactiae (S. agalactiae or GBS) is the main pathogen causing subclinical mastitis in dairy cows. This infection has seriously affected the development of the global dairy industry and thus requires urgent mitigation strategies to reduce its spread. Thus endophytes which are potential sources of novel bioactive antibacterial compounds can effectively be harnessed to address the issues of bacterial infections and resistance in animal production. The aim of this study was to investigate the in vitro antibacterial activity and potential mechanism of Bacillus velezensis Ea73 (an endophyte from Ageratina adenophora plant) cell free supernatant (CFS) against S. agalactiae isolated from cows. The antibacterial activity of Ea73 CFS against S. agalactiae was analyzed by plate and double dilution methods. Biofilm staining and transmission electron microscopy were used to explore the effects of Ea73 CFS on biofilm formation, structure and extracellular polymeric substances in the S. agalactiae. In addition, network pharmacology was used to further explore the relevant mechanisms of Ea73 CFS in treating diseases mediated by S. agalactiae. The results showed that the inhibition zone diameter of Ea73 CFS against S. agalactiae was 12 mm, and the minimum biofilm inhibition concentration was 10 mg/mL. After treatment with Ea73 CFS, the biofilm formation was significantly inhibited, the structure of the generated biofilm was disrupted, and the metabolic activity of bacterial cells was significantly reduced. The results from this study indicated that EA73 CFS significantly inhibits S. agalactiae activity via biofilm eradication and hence can serve as a promising antibacterial reagent.